The evolution of research on corporate social responsibility and financial performance: a bibliometric analysis - Phathutshedzo Lemana; Reon Matemane; Maatabudi Mokabane (Cogent Business & Management)
The evolving interplay between corporate social responsibility performance (CSRP) and financial performance (FP) has emerged as a pivotal area of inquiry, prompting renewed interest among scholars and practitioners. This article embarks on a comprehensive literature review that spans peer-reviewed studies from 1989 to 2024 with the aim of elucidating the intricate dynamics between CSRP and their impacts on FP. A meticulous, systematic analysis of 508 scholarly articles indexed in Scopus originating from both accounting and non-accounting journals serves as the empirical foundation for this exploration.The bibliometric analysis reveals a noteworthy growth trajectory in the CSRP-FP literature, particularly pronounced in the post-2008 period, with Asian nations, most prominently China, India, and South Korea, emerging as leaders in this scholarly domain driven by supportive governmental frameworks. Notable contributors to the field include key authors such as Lee and Lin, who meticulously identify influential keywords and journals alongside critical affiliations that define the CSRP-FP research landscape.The insights garnered from this investigation provide a rigorous roadmap for future academic inquiries, emphasising the evolution of key themes and collaborative mechanisms that underpin corporate social responsibility practices. This study represents a pioneering effort to conduct a comprehensive bibliometric analysis focusing on the geographical and disciplinary contours of CSRP and FP studies. By illuminating significant authors, impactful journals, and essential terminologies, this study enhances the understanding of the multifaceted relationship between CSR initiatives and their financial implications, thereby contributing novel perspectives to the existing body of knowledge.